Alza y volatilidad en los precios de los alimentos: oportunidades y desafíos para la seguridad alimentaria y nutricional en Centroamérica - Soto Baquero , Fernando; Rapallo, Ricardo (Revista Española de Desarrollo y Cooperación, 2023)
This article begins by pointing out the major features of the current level of food prices and its medium-term prospects. Next It is analyzed the consequences of this phenomenon for Central America, and concludes by suggesting three major areas of public policy to be strengthened in the coming years to help in improving the capacities of countries to ensure Food Security and Nutrition for their citizens.